1. ## Exact equation

I already know this equation is not exact. The thing is, I never learned how to do partial derivatives so that is what I need help with. The equation is $\displaystyle (e^xsiny+3y)dx-(3x-e^xsiny)dy=0$
I know that the sign in the middle needs to be + so then you have $\displaystyle (e^xsiny+3y)dx+(-3x+e^xsiny)dy=0$.
Then M=$\displaystyle e^xsiny+3y$ and N=$\displaystyle -3e^x+e^xsiny$. So, I need help getting $\displaystyle M_y and N_x$.

2. Originally Posted by steph3824
I already know this equation is not exact. The thing is, I never learned how to do partial derivatives so that is what I need help with. The equation is $\displaystyle (e^xsiny+3y)dx-(3x-e^xsiny)dy=0$
I know that the sign in the middle needs to be + so then you have $\displaystyle (e^xsiny+3y)dx+(-3x+e^xsiny)dy=0$.
Then M=$\displaystyle e^xsiny+3y$ and N=$\displaystyle -3e^x+e^xsiny$. So, I need help getting $\displaystyle M_y and N_x$.
To do partial derivatives, just hold all other variables that u r not taking the derivative constant

So
$\displaystyle M_y = e^xcosy+3$
and
$\displaystyle N_x = -3e^x+e^xsiny$